Ayurvedic Management of Haematohidrosis - A Case Report - Beena , K G (International Research Journal of Ayurveda & Yoga, 2022)
Introduction: Haematohidrosis is a very rare disease in which bleeding occurs from the surface of the body and through intact skin and the external orifices without any physical stress or trauma. Methods - Case presentation: A 21-year-old male patient reported with a history of recurrent episodes of bleeding from the eyes, nose, mouth and occasionally from the scalp. There was no fever or pain and the bleeding was self-limited. The disease was diagnosed as haematohidrosis as per the symptoms. The disease is similar to Raktapita described in Ayurveda. Ayurvedic medicines along with counseling were given in different periods within one year. Drugs with Rakta sthambana, Seeta veerya and Medya property were selected for treatment. Follow-up was done for four years. Results & discussion: Specific treatment protocol for the treatment of haematohidrosis is not available. Ayurvedic drugs selected based on symptoms of Raktapita along with counseling were found very effective. The patient has not had any episodes of bleeding for the last four years and he is leading a peaceful life.